INFORMATION AND COMMUNICATION TECHNOLOGIES IN TECHNICAL (ICTS) AND VOCATIONAL EDUCATION AND TRAINING (TVET) FOR INTEGRATION TOWARD KNOWLEDGE MANAGEMENT (Journal of Engineering and Health Sciences, 2022)
The relevance of Information and Communication Technology (ICT) in the field of Technical Vocational Education and Training (TVET) cannot be overemphasized in community studies. The era of work is changing constantly like ICT, thus creating more challenges for workers in the face of the current globalization in the 21st century and the University responsible for its provision. Although many studies explain and demonstrate the extent to which ICT is applied to different educational disciplines, the literature on effective ICT integration in the field of Technical Education and Training (TVET) is limited and requires further exploration to highlight the level of TVET requirements for ICT integration. Therefore, this paper attempts to add to the ICT integration in TVET by making it clear; the need for effective ICT integration in TVET, the factors that influence effective ICT integration in TVET, the overview of the challenges for effective ICT integration in TVET. This paper proposes for the planning and management of ICT resources on TVET.